Improving the Analytical Reproducibility of Electrochemical Capacitive Sensors Using the Chemical Hardness of the Interface - Corzo, Sandra P.; Bueno, Paulo R. [UNESP]; Miranda, David A. (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Miranda and Bueno recently demonstrated that chemical hardness could be experimentally measured and used as a chemical reactivity index of electrochemical interfaces. Herein, we applied this reactivity index concept to sense biological targets of medical interest, demonstrating the advantages of using this concept in improving the reproducibility of signal analysis during the construction of analytical curves. An analytical signal was obtained for sensing based on the effective chemical hardness of the quantum capacitive electroactive moieties of the interface, demonstrating advantages for calibration compared with methods based solely on the inverse of capacitance. The clinical value of this concept was demonstrated by studying the biological interaction of paclitaxel withβ -tubulin.
Keywords: Analytical curve; Calibration procedure; Conceptual density functional theory; Electrochemical sensor; Quality control and reproducibility; Quantum capacitance